2012
DOI: 10.1038/sc.2011.187
|View full text |Cite
|
Sign up to set email alerts
|

Patients with traumatic spinal cord injuries and their satisfaction with their general practitioner

Abstract: Patients with incomplete SCI were least satisfied probably because their physicians do not acknowledge their complicated medical complaints and do not meet the patient's expectations. Patients with anxiety and/or depression were more likely to report low satisfaction with their GP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…21 A previous study from Norway found that patients with incomplete SCI were least satisfied probably because their physicians do not acknowledge their complicated medical complaints and do not meet the patient's expectations. 22 This survey was, however, not powered to answer whether it makes a difference from where the patients get their information, and there is a lack of published studies on this topic.…”
Section: Hagen and Rekand Management Of Bladder Dysfunction In Sci Pamentioning
confidence: 99%
“…21 A previous study from Norway found that patients with incomplete SCI were least satisfied probably because their physicians do not acknowledge their complicated medical complaints and do not meet the patient's expectations. 22 This survey was, however, not powered to answer whether it makes a difference from where the patients get their information, and there is a lack of published studies on this topic.…”
Section: Hagen and Rekand Management Of Bladder Dysfunction In Sci Pamentioning
confidence: 99%
“…If we use our sample as representative of Prekmurje Roma, almost all (96.4%) are registered with an FP. Patients with chronic diseases are frequent attendees at FP clinics and are satisfied with them ( 11 , 48 , 49 ). They have increased anxiety and depression with lower perceived HRQoL ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…This means that the increasing CVD, diabetes mellitus, COPD and mental health problems are a big burden on the Roma communities ( 5 9 ). Only a few studies have assessed the impact of ethnicity on HRQoL in non-communicable diseases, but these studies indicated that Roma ethnicity is associated with a lower mental as well as physical HRQoL ( 5 , 10 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with SCI, however, often find that their family doctor does not fully appreciate the complexity of their situation, or the limitations their disability imposes on the options for health promotion and care [ 4 ]. Family physicians themselves report that managing patients with disabilities like spinal cord injury is challenging [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%